Plan de Mejora de Procesos, Utilizando el ERP-ODOO en el Macroproceso de Ventas de la Empresa Construcciones Centenario E. I. R. L. de la Ciudad de Huaral 2022 (LACCEI, 2024)
Currently, technology has become an important tool and, in many cases, essential to be at the forefront and advance in various fields, including the business field. In recent years, one of the most used technological solutions in companies has been the ERP-type system since, through a friendly and predictable interface, it is capable of connecting the most important areas of a company and automating the processes involved. This research aims to develop a process improvement plan, using the ERP ODOO in the sales macro-process of the company CONSTRUCCIONES CENTENARIO E. I R. L. As a method of data collection, surveys, remote interviews with senior management were used and the oldest workers of the company and review of informative documents. After the implementation, the result is that the time for preparing sales reports is reduced by 99.65% with respect to the previous process, reflecting a very noticeable optimization. It should be noted that the new reports generated with the ERP, unlike the previous reports, have information ordered by relevance, adapted to the needs of the applicants. Finally, the implementation of the ERP ODOO with respect to the sales macroprocess has a positive influence on the execution of the aforementioned macroprocess in the company CONSTRUCCIONES CENTENARIO E. I. R. L.